Sensing Properties of ZnO-SWCNT Hybrid Nanostructure Coated on Flexible Substrate for CO2 Gas Detection - Aisyah Nur Estri (Jurnal Sains Materi Indonesia, 2022)
We report sensing properties of functionalized single walled carbon nanotubes (f-SWCNTs) deposited on the flexible substrate of silicon (Si)  and polyethylene tereptaphalate (PET).  Deposition of f-SWCNT  on Si rubber and PET surface was conducted by applying different manner  of  spray coating and dip coating  techniques, respectively. Surface modification of f-SWCNT by ZnO nanostructure layer were applied by hydrothermal process.The research study  were conducted to know the effect of substrate material and ZnO structure on the f-SWCNT surface which embedded in those flexible polymer substrates. The results reveal that f-SWCNT on Si substrate (f-SWCNT/Si) do not have a good  response in gas sensing performance. In meanwhile  f-SWCNT on PET substrates (f-SWCNT/PET) is more sensitive about 1.6% with 3s in response.  ZnO structure layer modifying the surface structure of f-SWCNT enhance the sensitivity and responsiveness of the sensor with sensitivity of 4.1 % in 2s response after CO2 injection. Effect of bending treatment of the sensor and its stability were further investigated. Morphological surface of f-SWCNT network and crystal structure of ZnO and f-SWCNT were also observed by scanning electron microscope (SEM) and X-ray diffraction, respectively